Software Technologies 10th International Joint Conference, ICSOFT 2015, Colmar, France, July 20-22, 2015, Revised Selected Papers - Lorenz, Pascal; Cardoso, Jorge; Maciaszek, Leszek A.; van Sinderen, Marten (Communications in Computer and Information Science, 2016)
This book constitutes the thoroughly refereed proceedings of the 10th International Joint Conference on Software Technologies, ICSOFT 2015, held in Colmar, France, in July 2015. The 23 revised full papers presented were carefully reviewed and selected from 117 submissions. The papers are organized around the following conference tracks: enterprise software technologies; software project management; software engineering methods and techniques; distributed and mobile software systems. .